Participatory planning and quality assessment: contributions of a nursing management technology - Lara Vandresen; Denise Elvira Pires de Pires; Maria Manuela Martins; Elaine Cristina Novatzki Forte; Jorge Lorenzetti (Universidade Federal do Rio de Janeiro, 2019)
ABSTRACT Objective: to analyze the outcomes of participatory planning and quality assessment of the nursing care provided in a hospital ward using a nursing management technology. Method: Convergent care research focuses on research and practice intervention, developed in a hospital in southern Brazil from April to August 2016. Participatory planning and quality evaluation was performed using the PRAXIS® technology. Results: In the participatory planning, a survey of needs/problems was carried out by 33 professionals followed by 5 workshops, where mission, guiding principles, 4 priority problems, expected results, objectives and plans of activities were defined. For quality evaluation, two indicators were used: satisfaction and notification of adverse events. The evaluation was carried out with 101 patients and /or relatives, predominating "great or good". Adverse events, 28 records, predominating medication errors. Conclusion: Participatory planning and quality assessment are essential to improve nursing care management and the PRAXIS® technological innovation has been a useful resource.